Biomass and trait biogeography of cephalopods on the European and North American continental shelves - Daniel Ottmann; Ken H. Andersen; P. Daniël van Denderen (Global Ecology and Biogeography, 2024)
Aim We evaluate whether the biomass and trait biogeography of cephalopods follow the distribution expected by metabolic theory for ectotherms with rapid growth and high metabolic rate. Location Continental shelves of the North Atlantic and Northeast Pacific oceans; global marine ecoregions. Time Period 1968–2020. Major Taxa Studied Cephalopods and fishes (Chondrichthyes and Osteichthyes). Methods We map the biomass of cephalopods and their traits across marine shelves using scientific bottom trawl survey data from the North Atlantic and Northeast Pacific. We further map global fisheries catch. We apply statistical methods to evaluate how temperature, zooplankton productivity and depth drive these patterns. Results Cephalopods represent a small fraction (1%) of the combined fish and cephalopod biomass on continental shelves. However, their distribution displays a high regional heterogeneity, with some areas being virtually absent of cephalopods and other areas accounting for up to 24% of total biomass. Higher temperatures and zooplankton productivity are associated with increased cephalopod biomass and proportional biomass relative to fish. The largest cephalopods are found in the Northeast Pacific. Growth rates are highest in warmer waters with fastest growth rates found in lower latitudes of the North Atlantic. Cephalopods constitute 5% of the combined fish and cephalopod global fisheries catch. This proportion varies across regions. Higher temperature and zooplankton productivity are associated with increased cephalopod catch relative to fish. Main Conclusions Temperature and productivity shape the large‐scale biogeography of cephalopods and their traits on marine shelves. The relations with temperature suggest that future warming could lead to a proliferation of fast‐growing cephalopods in cold and temperate systems, with implications for ecosystem dynamics and fisheries. Despite a relatively low observed biomass, cephalopods hold substantial potential to change ecosystem structure and functioning given their high energy lifestyle.

Model of mesopelagic fish predation on eggs and larvae shows benefits of tuna spawning under full moon - Daniel Ottmann; Tom J. Langbehn; Patricia Reglero; Diego Alvarez‐Berastegui; Øyvind Fiksen (Limnology and Oceanography, 2023)
Most mesopelagic fish are small planktivores that migrate up at nightfall to feed in the safety of darkness and descend to depth at dawn to escape visual predators. However, the trophic roles can reverse since mesopelagic fishes also predate eggs and larvae of their predators. We use the Atlantic bluefin tuna as a model species to test the hypothesis that fishes in the open ocean synchronize spawning to moon‐lit nights (when mesopelagic fishes avoid near‐surface waters) to increase offspring fitness. Our analysis over two decades of field observations shows that tuna spawn most intensively the week before full moon. This fits predictions from a mechanistic model where spawning around full moon increases offspring fitness by two orders of magnitude due to low predation from mesopelagic fishes. Circalunar patterns of food availability can also favor fitness of offspring spawned the days before full moon. Our findings suggest that mesopelagic fishes may have an important impact on pelagic fish through predation of early life stages and cause an evolutionary drive to synchronize spawning to the lunar cycle.

Seasonal variability of phytoplankton community response to thermal discharge from nuclear power plant in temperate coastal area - Jingjing Zhang; Yibin Wang; Daniel Ottmann; Peng Cao; Jisong Yang; Junbao Yu; Zhenbo Lv (Environmental Pollution, 2023)

Spawning site distribution of a bluefin tuna reduces jellyfish predation on early life stages - Daniel Ottmann; Øyvind Fiksen; Melissa Martín; Francisco Alemany; Laura Prieto; Diego Álvarez‐Berastegui; Patricia Reglero (Limnology and Oceanography, 2021)
Bluefin tunas across the world migrate long distances to spawn in particularly warm and oligotrophic areas constrained by oceanographic fronts. The low abundance of predators in these areas increases survival chances of their early life stages, but its importance for choice of spawning habitat is unknown. Here, we use estimated clearance rates and data on spatial distributions of Atlantic bluefin tuna larvae Thunnus thynnus and metaephyrae of the jellyfish Pelagia noctiluca to quantify predation at a major spawning ground in the Mediterranean Sea. We found that high densities of P. noctiluca can rapidly deplete tuna eggs and preflexion larvae, but their patchy distribution and low spatial and temporal overlap results in overall low predation. The specific distribution of the spawning sites suggests that bluefin tunas may use local oceanography as cues to spawn outside areas with high predator densities.